Perencanaan dan Perancangan Sirkuit Drag Race Sebagai Sarana Untuk Memfasilitasi Hobi Balapan di Klungkung - I Kadek Yandi Putra; I Nyoman Warnata; I Ketut Sugihantara (Undagi : Jurnal Ilmiah Jurusan Arsitektur Universitas Warmadewa, 2021)
The drag race event is held annually in Klungkung, on July 20 2014 the 2014 Drag Bike Cup Regent event was held, then on February 14 2016 the Klungkung Regent Drag Bike event was held, then on May 19 2019 the 2019 Drag Bike Championship event was held, the three of them took place at By Pass Ida Bagus Mantra, Kusamba, Klungkung due to the unavailability of circuit facilities that could accommodate the drag event in Klungkung. Until now, Klungkung Regency and even Bali Province does not yet have a circuit that accommodates drag activities, this results in outside official racing events, racing hobbyists still carry out illegal racing or illegal racing, the main factor as a cause of wild racing, namely the absence of racing circuit facilities, making automotive lovers choose highway instead (Lismaharia Febry, 2017). The Drag Race circuit is planned to accommodate the activities of people who have a hobby of drag racing, later the community can channel their hobby of drag racing such as holding official competition events, as well as testing vehicles and driving skills outside official events quietly at the Drag Race Circuit without having to fear disturbing order on public roads and unsettling the general public. In addition, the Drag Race Circuit can serve as a means of education and entertainment for the general public that the hobby of drag racing is not as bad as what the general public has imagined so far.